Impact of Board Composition and Ownership Structure to Dividend Policy with Profitability as Moderating Variable - Alwan Ayyasyi; Rico Akbar Rianto; Susy Muchtar (UNIVED Press, 2026)
This research investigates the impact of board composition and ownership structure on dividend policy, with profitability serving as a moderating variable. Board composition is represented by Board Size and Board Independence, while ownership structure is described by Institutional Ownership and Managerial Ownership. Profitability, measured by Return on Equity (ROE), acts as the moderating variable. Using a purposive sampling technique, the study analyzed 47 manufacturing firms listed on the Indonesia Stock Exchange that consistently distributed dividends from 2020 to 2024, resulting in 235 firm-observations. Panel data regression with the Common Effect Model (CEM) was employed for analysis, as determined by Chow, Hausman, and Lagrange Multiplier tests. The findings reveal that Board Size, Board Independence, Institutional Ownership, and Managerial Ownership all exert a significant positive effect on Dividend Policy. However, Firm Size, included as a control variable, showed no significant influence on Dividend Policy. In terms of moderation, profitability does not significantly moderate the relationship between Board Size and Dividend Policy. Conversely, profitability significantly strengthens the positive relationships between Board Independence and Dividend Policy, Institutional Ownership and Dividend Policy, and Managerial Ownership and Dividend Policy, acting as a quasi-moderator in these relationships. Collectively, the independent variables, along with their moderating effects, explain 88.91% of the variation in Dividend Policy, indicating a strong simultaneous influence.